Bromodomain-containing protein 4 (BRD4) regulates RNA polymerase II serine 2 phosphorylation in human CD4+ T cells. - Zhang, W; Prakash, C; Prakash, C; Sum, C; Sum, C; Gong, Y; Gong, Y; Li, Y; Li, Y; Kwok, J; Kwok, J; Thiessen, N; et al. (2013)
Transcriptional elongation by RNA polymerase II (Pol II) is regulated by positive transcription elongation factor b (P-TEFb) in association with bromodomain-containing protein 4 (BRD4). We used genome-wide chromatin immunoprecipitation sequencing in primary human CD4+ T cells to reveal that BRD4 co-localizes with Ser-2-phosphorylated Pol II (Pol II Ser-2) at both enhancers and promoters of active genes. Disruption of bromodomain-histone acetylation interactions by JQ1, a small-molecule bromodomain inhibitor, resulted in decreased BRD4 binding, reduced Pol II Ser-2, and reduced expression of lineage-specific genes in primary human CD4+ T cells. A large number of JQ1-disrupted BRD4 binding regions exhibited diacetylated H4 (lysine 5 and -8) and H3K27 acetylation (H3K27ac), which correlated with the presence of histone acetyltransferases and deacetylases. Genes associated with BRD4/H3K27ac co-occupancy exhibited significantly higher activity than those associated with H3K27ac or BRD4 binding alone. Comparison of BRD4 binding in T cells and in human embryonic stem cells revealed that enhancer BRD4 binding sites were predominantly lineage-specific. Our findings suggest that BRD4-driven Pol II phosphorylation at serine 2 plays an important role in regulating lineage-specific gene transcription in human CD4+ T cells.